2019
DOI: 10.1088/1742-6596/1378/2/022051
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition Efficiency of Tamarindus Indica Leaves Extracts on Mild Steel in Hydrochloric Acid

Abstract: Tamarindus indica leaves extract was used as a green corrosion inhibitor for mild steel in 1 M hydrochloric acid (HCl) under varied conditions using weight loss technique. The inhibition efficiency, thermodynamics, kinetics and mechanism of inhibition by Tamarindus indica leaves extract on the mild steel were determined. The inhibitor’s concentrations used for the study were 0.0g/15ml (blank), 0.2g/15ml, 0.4g/15ml, and 0.6g/15ml, at the temperatures of 28°C (301K), 40°C (313K), 50°C (323K), and 60°C (333K). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 14 publications
3
5
0
Order By: Relevance
“…Ogunleye et al [16] calculated the values of ∆G 0 ads for Luffa cylindraca leaf extract at 333 K, which ranged between −11.56 and −11.45 kJ/mol. Similar findings were also presented by Nchewi et al [83] for Tamarindus indica leaf extract tested at numerous temperatures. They obtained values between −1.47 and −1.57 kJ/mol.…”
Section: Inhibition Mechanismsupporting
confidence: 90%
See 1 more Smart Citation
“…Ogunleye et al [16] calculated the values of ∆G 0 ads for Luffa cylindraca leaf extract at 333 K, which ranged between −11.56 and −11.45 kJ/mol. Similar findings were also presented by Nchewi et al [83] for Tamarindus indica leaf extract tested at numerous temperatures. They obtained values between −1.47 and −1.57 kJ/mol.…”
Section: Inhibition Mechanismsupporting
confidence: 90%
“…The authors concluded that the protective layer on the metal surface is stable. The experiments conducted by Nchewi et al [83] and Fadhil et al [35] showed that the values of standard free energy are in parallel with the temperature of the acidic environment. This means that ∆G 0 ads increases as the environment becomes hotter.…”
Section: Inhibition Mechanismmentioning
confidence: 99%
“…The coupon's weight loss in the electrolyte with the C. maxima inhibitor is w1, while the coupon's weight loss in the electrolyte without the inhibitor is w2. The surface coverage of the inhibitor on the surface of the steel is θ, w1 and w2 (Equation 4) are the change in mass of stainless steel in solution with inhibitor and without inhibitor, respectively (Nchewi et al,2019;Madu et al, 2019).…”
Section: 𝑥 𝑊 𝜌𝐴𝑡mentioning
confidence: 99%
“…Kumar et al (2019) prepared the Tamarinds Indica extract using air and shaded dried different parts (leaves, stem bark and fruits) of Tamarinds Indica plant after grinding and ground to powdered, then soaking using ethanol and refluxed, free acids were removed by reaction with any base and then washing with chloroform. Nchewi et al (2019), extracted the leaves of Terminalia Catappa after washing and air drying at room temperature (28 6 3°C), soaking in ethanol for 48 hours, sieved with a muslin cloth, filtered and concentrated using a rotatory evaporator. Okoro and Mbaka (2020), prepared extract from Tamarindus Indica fruit husks after drying using sunlight, and at oven at 50°C, then grounding.…”
Section: Tamarindus Indicamentioning
confidence: 99%
“…The corrosion inhibition property of Tamarindus Indica is gaining much attention. The corrosion inhibition property of tamarind shell, seed, pulp and leaves was studied, Table 1., (Jayakumar et al, 2020;Khalid et al, 2016;Kumar et al, 2019;Limsangouan, 2020;Nchewi, 2019;Okoro and Mbaka, 2020;Oluseyi and Temitayo, 2015;Sharma et al, 2015). Rao et al (2013) showed that a ternary inhibitor formulation consisting of N,N-Bis (phosphonomethyl) glycine (BPMG), Zn2, and tartrate inhibits corrosion of carbon steel in solutions of various pH levels.…”
Section: Use Of Tamarindus Extract As Corrosion Inhibitorsmentioning
confidence: 99%